Medical Therapy in Urology - Shergill, I. S.; Arya, Manit; Grange, Philippe R.; Mundy, A.R.; SpringerLink (Online service) (London : Springer London, 2010)
Medical Therapy in Urology is a concise and practical guide to the medical management of urological diseases. Bridging the gap between primary and secondary care, it provides clinicians in an outpatient setting, including family practitioners, with the information needed for the initial medical management of urological conditions. The editors and authors bring a wealth of experience in Urology to ensure that the primary care practitioner is completely equipped to initiate the treatment and management of all manner of urological conditions. Each chapter includes a brief overview of the relevant anatomy, physiology and pathology of the condition in question, an explanation of the drugs used , a review of medical literature and a clinical section on when a particular drug treatment should be used. Consultant Urologists, Uro-radiologists, medical clinicians and family practitioners alike will find this succinct overview a valuable resource in their day-to-day practice.
Bladder Cancer -- Renal Cell Cancer -- Prostate Cancer -- Testicular Cancer -- Penile Cancer -- LUTS/Benign Prostatic Hyperplasia -- Overactive Bladder and Incontinence -- Urinary Tract Infections -- Bladder Pain Syndrome/Interstitial Cystitis -- Chronic Prostatitis/Chronic Pelvic Pain Syndrome -- Urinary Tract Stones -- Erectile Dysfunction -- Male Hypogonadism -- Renal Transplantation -- Analgesia for Urological Procedures -- Alternative or Complementary Treatments in Urology.
Keywords: Medicine; Emergency medicine; Family medicine; Urology; Medicine & Public Health; Urology/Andrology.; General Practice / Family Medicine; Emergency Medicine; Primary Care Medicine